Benefit Generosity and Injury Duration: Quasi-Experimental Evidence from Regression Kinks - Benjamin Hansen; Tuan Nguyen; Glen R. Waddell (Institute of Labor Economics (IZA), 2017)
In this paper, we investigate the effect of benefit generosity on claim duration and temporary benefits paid among temporary disability claims for workers' compensation. While previous studies have focused on natural experiments created by one-time large changes in minimum or maximum weekly benefits, we exploit variation around a kink in benefit generosity inherent in all workers' compensation systems in the United States. Using administrative data on the universe of injured workers in Oregon, we also find that more-generous benefits leads to longer injuries, but with implied elasticities that are smaller than the average elasticity from previous difference-in-difference studies. Our preferred estimates suggest that a 10-percent increase in benefit generosity leads to a 2- to 4-percent increase in injury duration. We derive similar duration-benefit elasticities when studying changes in benefits paid at the kink. We also introduce the first evidence that more-generous benefits encourage subsequent claim filing.
Keywords: I18; J33; J53; 330; worker compensation; moral hazard; regression kink